A new approach to modelling initial dilution of a buoyancy-dominated jet in moving water. Issue 2 (1st March 2002) - Lye, L M; ,; Sharp, J J
Abstract : Initial dilution is one of the most important measures in the design of ocean outfalls. Considerable efforts have been devoted in the past to modelling initial dilution of a buoyancy-dominated jet in moving water. This paper reviews available initial dilution models and presents a new modelling approach based on a length scale analysis combined with an additive entrainment hypothesis, and nonlinear regression modelling. The proposed approach is more systematic and more justifiable than existing methods for two reasons: (1) it uses an objective measure to evaluate the model and (2) it includes the effect of ambient current in the buoyancy-dominated near field (BDNF). Using available experimental data, a new, continuous, initial dilution model is proposed and compared with presently available models. The proposed model is presented in both deterministic and probabilistic form.